Mokslinių komunikacijų normų ir normatyvų problema - Malcienė, Liliana (Knygotyra, 2026)
Under present conditions further development of science depends on the level of scientific information activities, thus it is very important to improve information service for scientists.It is believed that at the formation of a new informatic paradigm all the structures and character of scientific communication will change essentially.Great attention, at present, is paid to meet constantly growing needs of scientists for information. But the character of qualitative changes arising due to changes in scientific paradigm is ignored. The article suggests to add new data of such scientific communication methods to the now existing system that provide information to scientists which could improve and make simpler the process of obtaining information from the point of view of the scientist.